Practical cut‐offs for visual rating scales of medial temporal, frontal and posterior atrophy in Alzheimer's disease and mild cognitive impairment. (13th April 2015) - Ferreira, D.; Cavallin, L.; Larsson, E.‐M.; Muehlboeck, J.‐S.; Mecocci, P.; Vellas, B.; Tsolaki, M.; Kłoszewska, I.; Soininen, H.; Lovestone, S.; Simmons, A.; Wahlund, L.‐O.; et al.
Abstract Background Atrophy in the medial temporal lobe, frontal lobe and posterior cortex can be measured with visual rating scales such as the medial temporal atrophy (MTA), global cortical atrophy – frontal subscale (GCA‐F) and posterior atrophy (PA) scales, respectively. However, practical cut‐offs are urgently needed, especially now that different presentations of Alzheimer's disease (AD) are included in the revised diagnostic criteria. Aims The aim of this study was to generate a list of practical cut‐offs for the MTA, GCA‐F and PA scales, for both diagnosis of AD and determining prognosis in mild cognitive impairment (MCI), and to evaluate the influence of key demographic and clinical factors on these cut‐offs. Methods AddNeuroMed and ADNI cohorts were combined giving a total of 1147 participants (322 patients with AD, 480 patients with MCI and 345 control subjects). The MTA, GCA‐F and PA scales were applied and a broad range of cut‐offs was evaluated. Results The MTA scale showed better diagnostic and predictive performances than the GCA‐F and PA scales. Age, apolipoprotein E (ApoE) ε4 status and age at disease onset influenced all three scales. For the age ranges 45–64, 65–74, 75–84 and 85–94 years, the following cut‐offs should be used. MTA: ≥1.5, ≥1.5, ≥2 and ≥2.5; GCA‐F, ≥1, ≥1, ≥1 and ≥1; and PA, ≥1, ≥1, ≥1 and ≥1, respectively, with an adjustment for early‐onset ApoE ε4 noncarrier AD patients (MTA: ≥2, ≥2, ≥3 and ≥3; and GCA‐F: ≥1, ≥1, ≥2 and ≥2, respectively). Conclusions If successfully validated in clinical settings, the list of practical cut‐offs proposed here might be useful in clinical practice. Their use might also (i) promote research on atrophy subtypes, (ii) increase the understanding of different presentations of AD, (iii) improve diagnosis and prognosis and (iv) aid population selection and enrichment for clinical trials.